Collateral management : a guide to mitigating counterparty risk - Simmons, Michael, 1951- (Wiley finance series, 2018)
Insight into collateral management and its increasing relevance in modern banking In the wake of recent financial crises, firms of all sizes have adjusted their policies to incorporate more frequent instances of collateral management. Collateral Management: A Guide to Mitigating Counterparty Risk explains the connection between the need for collateral management in order to alleviate counterparty risk and the actions that firms must take to achieve it. Targeted at middle and back office managers seeking a hands-on explanation of the specifics of collateral management, this book offers a thorough treatment of the subject and attends to details such as internal record management, daily procedures used in making and receiving collateral calls, and settlement-related issues that affect the movements of cash and securities collateral. An expert in financial topics ranging from trade lifecycle to operational risk, author Michael Simmons offers readers insight into a field that, so far, is struggling to produce enough expertise to meet its high demand. Presents hands-on advice and examples from a bestselling, internationally renowned author who introduces his third book on operations and operations-related activities Explains the relationship between collateral management and preventing institutional defaults, such as the recent Lehman Brothers downfall Since 2008, firms have recognized and embraced the importance of collateral management, but this book will provide practitioners with a deeper understanding and appreciation of its relevance.